The application of zeolite in reducing green house gases in agriculture field - Putra, Ketut Candra Pangestu; Masjud, Yunita Ismail (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: The addition of Zeolite 4A affected cumulative greenhouse emissions from rice. Zeolite 4A has been found to adsorb CH4 and CO2, reducing overall emissions. The combination of zeolite and fertilizer administration in one or two applications provided an anti-synergistic effect. Methods: The chemical fertilizers and sustained release organic fertilizers used were 16200, 4600 and 666, respectively, and the amount was 31.25 gm2. Findings: Higher fertilization stimulated harvesting, resulting in higher yields and higher proportions of good grain, but less efficient GHG reductions. The ratio of zeolite 4A to fertilizer should be higher than 3: 1 to reduce the increase in greenhouse gas emissions from the use of fertilizer. This treatment resulted in an emission reduction efficiency of 34.69% in proportion to 21.62 g CO2eq m2 g1 zeolite. Conclusion: In the current study, two applications, fertilizer and zeolite 4A, showed the best performance in reducing emissions. However, it is advisable to increase the ratio of zeolite to fertilizer. Similarly, sustained release organic fertilizers resulted in increased CH4 emissions due to the action of methanogens on organic matter. However, plant growth, good grain proportions, and total grain yields increased. Further research is recommended to investigate the optimal ratio of zeolite 4A to organic and synthetic fertilizers for rice cultivation.